(untitled) (Agro Productividad, 2021)
Objectives: To determine the chemical composition and in vitro digestibility of Acacia angustissima, Dalea spp., Desmodium spp., Leucaena leucocephala, Phaseolus vulgaris and Tephrosia vicioides (Fabaceae) fodder species. Design/Methodology/Approach: Crude protein (CP), neutral detergent fiber (NDF), acid detergent fiber (ADF), crude lignin (CL), cellulose (Cel), hemicellulose (Hcel), cellular content (CC) and in vitro dry matter digestibility (IVDMD) were determined. The design was completely random with three repetitions. The variables were correlated by pairs and the means of the species were compared with Tukey’s test (P<0.05). Results: Dalea spp. had the highest crude protein (17.7%), followed by A. angustissima (15.9%) and L. leucocephala (14.1%). A. angustissima (73.2%), Dalea spp. (74.9%) and P. vulgaris (77.5%) showed the highest IVDMD. L. leucocephala, Tephrosia vicioides and Desmodium spp. showed the lowest values of CP (14.1, 11.8 and 12.3%, respectively) and IVDMD (70.4, 70.2 and 64.9%, respectively). Desmodium spp. showed high levels of NDF (59.2%), ADF (41.4%), CL (17.5%), Cel (29.7%) and Hcel (17.8%) (P?0.05). IVDMD showed positive correlation with CC and negative correlations with NDF, CL, and Hcel (P<0.05). Study Limitations/Implications: Desmodium spp. showed high content of CL and low values of CP and IVDMD, therefore supplements should be added when used in animal feed. Findings/Conclusions: Dalea spp. showed low levels of lignin and high levels of protein and digestibility, making it posible to use as feed for ruminants